2008
DOI: 10.1212/01.wnl.0000326589.57128.c3
|View full text |Cite
|
Sign up to set email alerts
|

Distinct CSF cytokine/chemokine profiles in atopic myelitis and other causes of myelitis

Abstract: Intrathecal upregulation of CCL11 and Th2 cytokines is characteristic of atopic myelitis, which is distinct from interleukin-17/interferon-gamma-related autoimmune condition of opticospinal multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 40 publications
(42 reference statements)
0
67
3
1
Order By: Relevance
“…The level of IL-9 is significantly increased in patients with atopic myelitis; however, this value was not elevated in our patient (17,18). Although MS is regarded to be a white matter disease, recent histopathological studies of early MS (25)(26)(27)(28)(29) have revealed lesions in the leptomeninges and gray matter to be important initial targets of the MS process.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The level of IL-9 is significantly increased in patients with atopic myelitis; however, this value was not elevated in our patient (17,18). Although MS is regarded to be a white matter disease, recent histopathological studies of early MS (25)(26)(27)(28)(29) have revealed lesions in the leptomeninges and gray matter to be important initial targets of the MS process.…”
Section: Discussioncontrasting
confidence: 68%
“…There were no oligoclonal IgG bands in the CSF. The pretreatment CSF cytokine/chemokine levels demonstrated elevation of type II helper T-cell (Th2) cytokines/ chemokines, such as eotaxin (4.73 pg/mL), IL-5 (22.2 pg/ mL) and IL-10 (12.19 pg/mL), compared with the findings of past studies regarding CSF cytokine/chemokine profiles (17,18). In contrast, the levels of INF-γ (<0.64 pg/ mL), IL-2 (0.91 pg/mL), IL-9 (5.02 pg/mL) and IL-17 (0.45 pg/mL) were not increased (Fig.…”
Section: Clinical Summarymentioning
confidence: 58%
“…Immunologically, AM appears to be different from other myelitis diseases associated with MS or HTLV-1-associated myelopathy/tropical spastic paraparesis in that type 2 helper T (Th2) cell response is predominant in the former whereas Th1 cell response is predominant in the latter [21][22][23]. More recently, CSF cytokine/chemokine analysis showing upregulation of chemokine-ligand-11/interleukin-9, which is important for eosinophil recruitment and maturation, has lent further supported the allergic nature of AM [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, atopic myelitis is distinguished from NMO by the absence of the anti-AQP4 antibody. In addition, CSF levels of IL-9 and CCL11/eotaxin are elevated in atopic myelitis cases, whereas in NMO patients CSF levels of Il-17 and interferon-g levels are elevated (Tanaka et al, 2008).…”
Section: Atopic Myelitis (Kira's Disease)mentioning
confidence: 95%